Smart Ecotourism: Integrating Technology into Sustainable Ecotourism Management - Susilawati, Eva; Sa'roni, Wahid Hasim; Herdiana, Emil (Almana : Jurnal Manajemen dan Bisnis, 2025)
This research is motivated by the challenges of ecotourism management in West Java, which despite its great potential, still faces problems of ecosystem degradation and suboptimal destination management. This study aims to develop a technology-based smart ecotourism model by integrating environmental, social, and economic aspects simultaneously, as a novelty from previous studies that generally only emphasize one aspect of management. The method used is a quantitative approach through a survey of 150 respondents consisting of ecotourism managers, tourists, and local communities in several leading destinations in West Java. Data were collected using a 1-5 Likert scale questionnaire and analyzed using validity and reliability tests, multiple linear regression, and path analysis with the help of SPSS 22. The results showed that the use of technology has a positive and significant effect on ecotourism sustainability (R² = 0.801, p < 0.05), but does not have a significant effect on the socio-economic impacts of the community, and ecotourism sustainability was not proven to mediate the relationship. The research conclusion emphasizes that technology integration needs to be accompanied by community empowerment programs to make socio-economic benefits more tangible, with recommendations in the form of increasing digital literacy, developing community-based platforms, and regional policies that support technology synergy and local welfare.